Life history research in educational settings learning from lives - Goodson, Ivor; Sikes, Patricia J. (Open University Press, 2001)
"It has long been recognized that life history method has a great deal to offer to those engaged in social research. Indeed, right from the start of the twentieth century, eminent sociologists such as W.I. Thomas, C. Wright Mils and Herbert Blumer have suggested that it is the best, the perfect, approach for studying any aspect of social life. In recent years, life history has become increasingly popular with researchers investigating educational topics of all kinds, including: teachers' perceptions and experiences of different areas of their lives and careers. Life History Research in Educational Settings sets out to explore and consider the various reasons for this popularity and makes the case that the approach has a major and unique contribution to make to understanding of schools, schooling and educational experience, however characterized. The book draws extensively on examples of life history research in order to illustrate theoretical, methodological, ethical and practical issue."--From back cover.